Análisis de los problemas de seguridad y redes en la empresa de internet Netline - Zamora Candelario, Helen Damaris (2022)
The purpose of network security is primarily to prevent damage from misuse of data. There are a number of potential problems that can occur if network security is not implemented correctly. Therefore, it is critical that any network administrator use strict policies to prevent potential loss, regardless of network size and type. It is a set of policies, regulations and arrangements developed by an administrator. For this, in the present case study, it is proposed to carry out the Analysis of the security and network problems in the Internet company Netline, considering as a critical factor to increase security to protect the important information of the company. It is necessary and important to have a vast knowledge about data networks, including all its components, and of course the necessary conditions must be implemented to be able to control access from external networks to the company's private network. The objective of this case study is Analyze the security and network problems in the internet company Netline. The field investigation will be used because it was necessary to resort to the place where the events take place. As a research tool, an interview with the head of systems of the company Netline was used. A questionnaire of questions was applied as an instrument. with the aim of finding the levels of computer security